The Disability Employment Puzzle: A Field Experiment on Employer Hiring Behavior. (March 2018) - Ameri, Mason; Schur, Lisa; Adya, Meera; Bentley, F. Scott; McKay, Patrick; Kruse, Douglas
The authors investigate potential discrimination against people with disabilities through a field experiment that sent job applications to 6, 016 accounting positions for which the applicants' disabilities are unlikely to affect productivity. One-third of the cover letters disclosed that the applicant had a spinal cord injury, one-third disclosed the presence of Asperger's syndrome, and one-third did not mention disability. The disability applications received 26% fewer expressions of employer interest. This gap was concentrated among experienced applicants and small private companies that are not covered by the Americans with Disabilities Act (ADA). Tests suggest possible positive effects of the ADA, but not of state laws, in reducing the disability gap. Results indicate there may be substantial room for employer and policy initiatives to improve employment opportunities for people with disabilities.